2012
DOI: 10.1016/j.carbon.2012.06.046
|View full text |Cite
|
Sign up to set email alerts
|

The use of small angle neutron scattering with contrast matching and variable adsorbate partial pressures in the study of porosity in activated carbons

Abstract: The porosity of a typical activated carbon is investigated with small angle neutron scattering (SANS), using the show that the resultant surface tension value is accurate for the larger pores but tends to increase for small (nanoscale) pores. The resultant pore size distribution is less model-dependent than for the traditional methods of analyzing the adsorption isotherms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…In the present experiments we have used the SANS technique previously developed for studies of activated carbon [5]. In particular, we have demonstrated that deuterated toluene also provides an excellent contrast matching liquid for graphites, condensing into all pores connected to the surface down to the minimum observable pore dimension ($0.2 nm).…”
Section: Contrast Matchingmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present experiments we have used the SANS technique previously developed for studies of activated carbon [5]. In particular, we have demonstrated that deuterated toluene also provides an excellent contrast matching liquid for graphites, condensing into all pores connected to the surface down to the minimum observable pore dimension ($0.2 nm).…”
Section: Contrast Matchingmentioning
confidence: 99%
“…An important result, known as the Porod Invariant (or Total Scattering), is the integral of the cross-section weighted by Q 2 , the value of which can be related to the volume fraction of the pores, u, so long as the cross-section is properly normalized, as it is here [5].…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of such atoms in bulk materials is negligibly small; however, it increases significantly for small particles. Contrast matching SANS was employed in [35] to measure the skeleton density of activated carbon powder produced from raw coal by steam activation. The experiments were performed using mixtures of normal and deuterated toluene of known composition.…”
Section: Contrast Variation With Liquids and Gasesmentioning
confidence: 99%